Durability Studies on Concrete Made Using Pulverized Used Foundry Sand as A Mineral Admixture - P M, Salim; S.R.K.Prasad, B; Sekhar.T, Seshadri (International Journal of Engineering and Technology, 2018)
Durability of the structures is a main concern now a day due to the various types of deteriorations caused by natural as well as manmade environmental conditions. In this project the durability properties of concrete made with pulverized used foundry sand as a mineral admixture is analyzed. The durability of concrete is mostly depends on the surrounding environment. The chemicals present in air and water are the main causes of deterioration of concrete in its life. So a deep study on the action of deteriorating chemicals on the concrete containing pulverized used foundry sand is initiated. Here M40 concrete is prepared with 0%,5%,10%,15% and 20% addition of pulverized used foundry sand to the cement content. Cubes of size 100mmx100mmx100mm were cast and tested for various parameters like Acid resistance with hydrochloric acid and sulfuric acid, Sulphate attack with sodium sulphate and alkali resistance with sodium hydroxide for. The testing was performed on cubes at 28day, 56 day, 90 day and 180 day stored in respective chemicals dissolved in water at 5% concentration. From the test results it is inferred that the concrete containing pulverized used foundry sand is better in acid resistance than ordinary concrete without pulverized used foundry sand. Further the acid resistance for both hydrochloric and sulfuric acid shows an increase up to 15% addition of pulverized used foundry and after that it is slightly reduced. The samples subjected to sodium sulphate and sodium hydroxide has shown no variation in properties with respect to the water cured specimens.Â Â
Keywords: Acid Resistance; Durability Factor; Mass Reduction Percentage; Pulverized Used Foundry Sand; Sulphate Attack